Lateral melt variations induce shift in Io’s peak tidal heating - Allard Veenstra; Marc Rovira-Navarro; Teresa Steinke; Ashley Gerard Davies; Wouter van der Wal (Nature Communications)
Abstract The innermost Galilean moon, Io, exhibits widespread tidally-driven volcanism. Monitoring of its volcanoes has revealed that they are not homogeneously distributed across its surface: volcanic activity is higher at low latitudes and peaks east of the sub- and anti-Jovian points. Dissipation in a radially symmetric solid body cannot explain the observed longitudinal shift but dissipation in a magma ocean can. However, recent observations show that Io does not have one. Here, we demonstrate that a longitudinal shift in the heating pattern naturally arises from the feedback between tidal heating and melt production. The feedback between tidal dissipation and interior properties that results in interiors that deviate from radial symmetry is expected to drive the interior evolution of other tidally-active worlds, including icy moons such as Europa and Enceladus and exo-planets/moons with high eccentricity or obliquity.